Customary Crimes and the Principle of Legality in the National Criminal Code - Anis Noviya (PT. Anagata Sembagi Education, 2026)
In the development of Indonesian criminal law, the recognition of living law through Law Number 1 of 2023 concerning the Criminal Code presents a new dynamic, particularly regarding the position of customary offenses in the national criminal law system. This condition has given rise to debate regarding the suitability of the recognition of unwritten customary norms with the basic principle of legality, which requires the formulation of crimes clearly and in writing. This study aims to analyze the construction of the legality principle in the national criminal law system and examine the position of customary offenses as living law in society from the perspective of the legality principle of the National Criminal Code. The research method used is normative legal research with a statutory approach, a conceptual approach, and a historical approach. The legal materials used include legislation, criminal law doctrine, and literature relevant to the concept of living law and the principle of legality. The results of the study indicate that the recognition of customary offenses in the National Criminal Code reflects an effort to integrate state law and customary law within the framework of Indonesian legal pluralism. This recognition is intended to accommodate social values ​​​​that exist in society and strengthen substantive justice. However, regulations regarding living law still leave unclear norms, particularly regarding the criteria for the applicability of customary norms that can be used as a basis for criminal penalties. This situation has the potential to create legal uncertainty and open up room for differing interpretations in law enforcement practices. Therefore, conceptual reconstruction and the formulation of clear parameters are needed to ensure that the recognition of customary crimes remains in line with the basic principles of legality, particularly the principles of lex scripta and lex certa, thereby ensuring legal certainty and the protection of human rights within the national criminal law system.